Hyperprogressive disease in non-small cell lung cancer treated with immune checkpoint inhibitor therapy, fact or myth? - Britt, Alec S.; Huang, Caitlyn; Huang, Chao H. (Frontiers in Oncology, 2022)
The therapeutic landscape for patients with non-small cell lung cancer (NSCLC) has dramatically evolved with the development and adoption of immune checkpoint inhibitors (ICI) as front-line therapy. These novel antibodies target the interactions in immunoregulatory pathways, between programmed death-1 (PD-1) and programmed death ligand-1 (PD-L1), or cytotoxic T-lymphocyte antigen 4 (CTLA-4) and B7, resulting in the activation of T cells and cytotoxic response to induce an immunologic response. ICIs have demonstrated significant survival benefits and sustained responses in the treatment of NSCLC leading to the long-term survival of up to 5 year. One unusual response to ICI is a phenomenon termed Hyperprogressive Disease (HYD), which occurs in a subset of patients for whom ICI therapy can induce rapid disease growth, which ultimately leads to poorer outcomes with an incidence rate ranging from 5 to 37% in NSCLC patients. Prior reviews demonstrated that HYD can be defined by rapid tumor progression, deterioration of patient’s symptoms or new onset of disease. The mechanism of HYD could be related to genomic and tumor microenvironment changes and altered immune response. It will be important to establish a common definition of HYD for future research and clinical care.